Gebrukothuria profundus, a new genus and species of laetmogonid holothurian (Elasipodida, Laetmogonidae) from around the Crozet Plateau in the Southern Indian Ocea - Rogacheva, Antonina; Cross, Ian A.; Billett, David S. M. (Zootaxa, 2009)
A new genus and species of laetmogonid holothurian (Elasipodida, Laetmogonidae), collected from around the Crozet Plateau in the Southern Indian Ocean, is described. It differs from other members of the family in that the body wall lacks the wheel-shaped calcareous deposits completely. Instead only rods are present. The genus is also distinguished by the combination of other morphological characters lacking in other known genera: absence of circum-oral and ventrolateral papillae together with development of midventral tube feet. All other members of the family Laetmogonidae are known to have wheel-shaped deposits, therefore diagnosis of the family is refined.